2021
DOI: 10.1002/jmri.27693
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium Clearance in the First 5 Weeks After Repeated Intravenous Administration of Gadoteridol, Gadoterate Meglumine, and Gadobutrol to rats

Abstract: Background Studies of gadolinium (Gd) clearance from animals in the first weeks after administration of gadolinium‐based contrast agents (GBCAs) have previously looked at solitary timepoints only. However, this does not give information on differences between GBCAs and between organs in terms of Gd elimination kinetics. Purpose To compare Gd levels in rat cerebellum, cerebrum, skin, and blood at 1, 2, 3, and 5 weeks after repeated administration of macrocyclic GBCAs. Study Type Prospective. Animal Model One hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Given the similar imaging performances of gadoteridol and gadobutrol and assuming similar commercial practicality, the choice of which GBCA to choose comes down to an evaluation of potential safety issues. Whereas prospective multicentre studies of gadobutrol and gadoteridol reveal no differences in terms of immediate contrast reactions [31][32][33][34], animal studies of gadolinium (Gd) retention suggest that gadoteridol is cleared much more from brain and other body tissues than gadobutrol [35][36][37][38][39] resulting in lower levels retained Gd for longer periods of time. However, no signs or symptoms associated with brain Gd retention have yet emerged despite concerted research effort [25][26][27][28], and while the possibility of long-term effects on human health is an area of concern [40], no data are yet available that point to differences between the macrocyclic GBCAs in terms of impact on long-term human health.…”
Section: Discussionmentioning
confidence: 99%
“…Given the similar imaging performances of gadoteridol and gadobutrol and assuming similar commercial practicality, the choice of which GBCA to choose comes down to an evaluation of potential safety issues. Whereas prospective multicentre studies of gadobutrol and gadoteridol reveal no differences in terms of immediate contrast reactions [31][32][33][34], animal studies of gadolinium (Gd) retention suggest that gadoteridol is cleared much more from brain and other body tissues than gadobutrol [35][36][37][38][39] resulting in lower levels retained Gd for longer periods of time. However, no signs or symptoms associated with brain Gd retention have yet emerged despite concerted research effort [25][26][27][28], and while the possibility of long-term effects on human health is an area of concern [40], no data are yet available that point to differences between the macrocyclic GBCAs in terms of impact on long-term human health.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas contraindication to linear GBCAs in patients with severe renal insufficiency effectively eliminated NSF as a risk associated with GBCA use, a report in 2014 [ 4 ] of increased signal intensity at magnetic resonance imaging in specific brain structures (primarily the dentate nucleus and globus pallidus) on unenhanced T1-weighted images of patients that had previously undergone multiple GBCA intravenous injections once again raised concern about GBCA safety. Subsequent demonstration of retained gadolinium (Gd) in brain tissue samples from decedents undergoing autopsy [ 5 ] and numerous demonstrations from studies in animals of retained Gd in brain and body tissues following multiple GBCA exposures [ 6 18 ] have confirmed that Gd is retained to a greater or lesser extent after administration of all GBCAs but that the greatest levels of retained Gd are seen after administration of linear nonionic GBCAs, i.e. , those with a clearer association with NSF.…”
Section: Introductionmentioning
confidence: 99%
“…A consequence of NSF and the demonstration of greater Gd retention after linear GBCA administration has been a move away from linear GBCAs towards a prevalent use of macrocyclic GBCAs for extrahepatic clinical applications. Among the macrocyclic GBCAs, gadoteridol (ProHance®) has been shown to result in lower levels of retained Gd compared to both gadobutrol (Gadovist®/Gadavist®) and gadoterate meglumine (Dotarem®/Clariscan®) in rats with normal renal function [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Semaglutide is a commonly used hypoglycemic drug in clinic, with exact efficacy on T2DM confirmed by many studies. However there are few reports mentioning the regulatory effect of this drug on glycolipid metabolism in patients with T2DM combined with NAFLD [3,4] . This study investigated the effect of semaglutide on glycolipid metabolism in patients with both T2DM and NAFLD.…”
mentioning
confidence: 99%